Penggunaan Teknologi Literasi Informasi dalam Kolaborasi Kemitraan sebagai Basis Pembelajaran di STIT Raden Wijaya Mojokerto menuju Era Digital Native - Yenny Imro'atul Mufidah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Information literacy promises a change that focuses on the development and use of information technology to improve the efficiency and effectiveness of education services. With regard to Online learning, the point of view has changed, that the learning environment is no longer centralized, but is distributed and open through learning features, facilitated by the Internet and network-based technology. This learning environment facilitates learning and knowledge development through meaningful interactions and actions. Ditulsinya This article aims to describe the Use of Information Literacy Technology in the Collaboration of Partnerships as a Learning Base at STIT Raden Wijaya Mojokerto towards the Digital Native Era. This research is library research Data obtained from books in the library and Internet media are secondary data. The data collection technique used by the authors in this study is documentation. The results of the discussion can be summarized as follows: 1). The sense of 'self' developing lecturer as teacher educator provides deep motivation beyond specific ways of working in a particular place. These beginner teacher educators have a broad workplace, working in various communities. 2). Shifting learning to digital with the presence of information and communication technology, especially computers and the internet has long been used by developed countries and it is time for STIT Raden Wijaya learning citizens to literate information literacy and carry out online learning activities at least to build communication and interaction through social networks such as Facebook, Twitter, online games, etc. for the benefit of partnership collaboration learning as a learning base. 3). In the future literacy competence is an absolute requirement for teachers at STIT Raden Wijaya.